2012
DOI: 10.5688/ajpe768150
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Workshop to Improve Mutual Understanding Between Pharmacy and Medical Students

Abstract: Objective. To measure changes in pharmacy and medical students' physician-pharmacist collaboration scores resulting from a workshop designed to promote understanding of the others' roles in health care. Methods. More than 88% of first-year pharmacy (n 5 215) and medical (n 5 205) students completed the Scale of Attitudes Toward Physician-Pharmacist Collaboration on 3 occasions in order to establish a baseline of median scores and to determine whether the scores were influenced by an interprofessional workshop.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 12 publications
0
43
0
1
Order By: Relevance
“…17,18 At Midwestern University, we used the instrument to show that even a single workshop exercise to foster understanding between medical and pharmacy students led to a small improvement in their physician-pharmacist collaboration scores. 21 We also found, however, that the collaboration scores of pharmacy students significantly exceeded those of medical students, and that this difference persisted even though medical students' scores improved after participating in the workshop. The effect size for the difference between pharmacy and medical students' collaboration scores was of crucial practical importance.…”
Section: Introductionmentioning
confidence: 75%
“…17,18 At Midwestern University, we used the instrument to show that even a single workshop exercise to foster understanding between medical and pharmacy students led to a small improvement in their physician-pharmacist collaboration scores. 21 We also found, however, that the collaboration scores of pharmacy students significantly exceeded those of medical students, and that this difference persisted even though medical students' scores improved after participating in the workshop. The effect size for the difference between pharmacy and medical students' collaboration scores was of crucial practical importance.…”
Section: Introductionmentioning
confidence: 75%
“…6,8,[22][23][24] Previous studies indicated that medical students often express skepticism regarding the utility of IPE. [25][26] Effective engagement of students in IPE requires all stakeholders, especially those in medicine, to be involved.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies found lower levels of enthusiasm for IPE training among students in medicine relative to students in other health care programs, including pharmacy, limited data is available to describe actual faculty member opinions and sentiments for IPE among the various health care professions. 6,8,[19][20][21] This study was conducted to explicitly examine potential differences in faculty member attitudes toward and interest in IPE along with perceived barriers among faculty members from osteopathic medicine, pharmacy , and physician assistant programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations